Introduction to librarianship - Gates, Jean Key (Neal-Schuman, 2004)
This book provides the fundametal elements of librarianship in sufficient detail to help the student acquire a foundation of historical backround; an understanding of major library objectives, services and needs; and an appreprication of librarianship as a profession and a career in preparation for the complex and specialized concepts and problems to be dealt with in later courses studies, and investigations